1998
DOI: 10.1055/s-2007-973560
|View full text |Cite
|
Sign up to set email alerts
|

Altered Antioxidant Enzyme Activities in Children with a Serious Adverse Experience Related to Valproic Acid Therapy

Abstract: Specific oxidative metabolites of valproic acid (VPA) have been associated with the clinically defined toxicity of the drug. To investigate the role of enzymatic detoxification in clinical toxicity, we compared activities of five antioxidant enzymes in 15 patients with a serious adverse experience (SAE) related to VPA therapy, to enzyme activities measured in 35 patients with good clinical tolerance of VPA, and 50 healthy, age-matched subjects. These enzymes included glutathione peroxidase (GSH-Px), glutathion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(57 citation statements)
references
References 1 publication
4
53
0
Order By: Relevance
“…Only a few articles describing abnormal FRSE activities in infants with MM have been published (6,7,8,10). Previous studies measured FRSE activities, especially GSH-related reported a similar observation.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Only a few articles describing abnormal FRSE activities in infants with MM have been published (6,7,8,10). Previous studies measured FRSE activities, especially GSH-related reported a similar observation.…”
Section: Discussionmentioning
confidence: 83%
“…Numerous studies have shown the relationship between FRs and neural tube defects (7, 8, 9, 10, 20, 29). The antiepileptic drugs producing FRs increase FR-mediated cellular damage and may result in neural tube defects (8,21,25,27). Exposure of rat embryos to a high concentration of oxygen (20%) during early neurulation (day 9 to 10) significantly increased the incidence of neural tube defects when compared with control embryos (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Erythrocyte GPX [91, 92], GR [93] and serum Se [94], uric acid and albumin [80], which are considered endogenous enzymatic and non-enzymatic antioxidant molecules, were found to be reduced in children and adults treated with VPA. Furthermore, in studies in patients with epilepsy, treated with VPA, increased levels of oxidative macromolecular damage markers, such as MDA [76, 86, 90, 91] and 15F-2t-isoP [95], which are markers of enhanced lipid peroxidation and increased levels of 8-OHdG [90, 96], which is a marker of nucleic acid damage, were observed.…”
Section: Antiepileptic Drug Therapy and Oxidative Stressmentioning
confidence: 99%
“…Increased oxidative stress and disturbance of the endogenous antioxidant system can aggravate seizure activity (Yüksel et al, 2000). On the other hand, data has shown that the metabolites of several AEDs behave as pro-oxidant agents with toxic effects (Graf et al, 1998;Niketic et al, 1995;Yüksel et al, 2000). Experiments have confirmed the potent antioxidant activity of melatonin in different pathological states: chronic melatonin infusion (10 mg/kg/day), as well as a cumulative dose of 10 mg/kg, suppressed KA-induced oxidative stress in the hippocampus (Chung and Han, 2003) without preventing the development of SE .…”
Section: Melatonin and Epilepsymentioning
confidence: 99%